RANCANG BANGUN APLIKASI CATUR MENGGUNAKAN ALGORITMA MINIMAX DENGAN OPTIMASI ALPHA-BETA PRUNING - Panji Novantara (Cloud Information, 2017)
ABSTRACT Chess is a strategy game which is played in turns. This game has been around since ancient times. In the game of chess, it requires strategy or a good way to win a game. It is one of sports that many people played. Almost everyone knows the game of chess, although some of them do not know the steps of the chess pieces. To determine a good movement in chess, we need an algorithm, one of them is the Alpha-Beta Pruning algorithm. Alpha-Beta Pruning is the development of MiniMax algorithm which is one of the searching algorithm to determine the maximum and minimum values by cutting unnecessary nodes. In this study, the writer makes an application chess game that anyone can play chess on an electronic device, especially PC, while the algorithm used is Alpha-Beta Pruning (specify the steps taken by the computer) with a software development method that is chosen is the Rational Unified Process (RUP ). In the process of implementing, these algorithms needs a method called evaluation board, in which each chess piece has a respective value of 0 is king, queen 900, 300 elephants, 300 horses, castle 500 and pawns 100. The results of this paper is the use of an algorithm Alpha-Beta Pruning in this chess game that the computer can respond to the steps taken by the users quickly.  Keywords : Chess, Minimax, Alpha-Beta Pruning, Node, RUP